STRATEGY FOR DETERMINING BEEF COMMODITY PRICES IN CONDITIONS OF FLUCTUATING US DOLLAR EXCHANGE RATE AGAINST THE RUPIAH USING A QUADRATIC EQUATION - Ambarita, Nita Priska (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Beef is a food commodity whose needs are mostly imported from other countries, so its selling value is greatly influenced by the US Dollar exchange rate. When the dollar exchange rate increases, sellers must adjust the selling price to avoid losses. The level of price elasticity of demand and changes in exchange rates are two variables that determine the price of beef. In this research, a model of changes in selling prices will be presented regarding the level of price elasticity of demand and changes in exchange rates in a simple quadratic equation model.